Altered platelet alpha 2 adrenoreceptor in acute myocardial infarction and its relation to plasma catecholamine concentrations. Issue 5 (May 1986) - Sakaguchi, K; Hattori, R; Yui, Y; Takatsu, Y; Susawa, T; Yui, N; Nonogi, H; Tamaki, S; Kawai, C
Abstract : Changes in platelet alpha 2 adrenoreceptors and their relation to plasma catecholamine concentrations were studied in 11 patients with acute transmural myocardial infarction. A radiolabelled alpha 2 adrenoreceptor antagonist, [3H]-yohimbine, was used to assay alpha 2 adrenoreceptors on platelet membranes, and plasma catecholamine concentrations were measured by high performance liquid chromatography. The number of platelet alpha 2 adrenoreceptors, the dissociation constant, and plasma noradrenaline and adrenaline concentrations were studied 6.6 (3.3) (mean (SD)) hours after the onset of acute myocardial infarction and one month later. The mean (SD) number of adrenoreceptors increased significantly from 94.5 (50.5) fmol/mg protein immediately after infarction to 157.0 (65.7) fmol/mg protein one month later. The dissociation constant, however, did not change significantly (4.33 (1.40) nmol/l vs 4.37 (1.22) nmol/l). Raised noradrenaline (5.60 (4.37) nmol/l) and adrenaline (0.28 (0.14) nmol/l) concentrations had fallen significantly to normal values (1.21 (0.67) and 0.09 (0.05) nmol/l respectively) a month after infarction. The decrease in the number of alpha 2 adrenoreceptors soon after infarction may be beneficial because such a change will reduce the strength of various reactions to catecholamines, such as vasoconstriction.